Pemikiran Ibnu Taimiyah Tentang Mekanisme Pasar dan Regulasi Harga di Indonesia masa Pandemi Covid-19 - Achmad Fajaruddin Fajaruddin; Indra Sholeh Husni; Meichio Lesmana Lesmana; Fini Shofiati Shofiati (ITB AAS INDONESIA Surakarta, 2023)
In recent years the world has been shocked by the emergence of the Coronavirus Disease 2019 (COVID-19) which has triggered a pandemic to occur evenly throughout the world. The Covid-19 pandemic has an impact on all aspects of life, especially in the economic sector. The purpose of this research is to find out Ibn Taimiyah's thoughts regarding market mechanisms and price regulation and to find out their relevance in Indonesia during the Covid-19 pandemic. The method in this research is the library method. The data analysis technique used the data reduction, data presentation, and data verification stages. The results of this study are that according to Ibnu Taimiyah a good market mechanism is one where price determination is formed naturally from market demand and supply and good price regulation is based on deliberations between government representatives, sellers and buyers. Ibnu Taimiyah's thoughts regarding market mechanisms and price regulations are very relevant if used as a basis and reference in carrying out economic activities in Indonesia during the Covid-19 pandemic. The government is expected to play a maximum role in dealing with problems in the Covid-19 pandemic in order to realize better benefits and improve the economy.